Effectiveness of 12 weeks of electrical vestibular nerve stimulation in the management of obesity: A pilot study - Goothy, Sai Sailesh kumar; Santoshkumar Bhise; Shyma Parapurath; Anita Choudhary; Sudhir Gawarikar; Rajagopalan Vijayaraghavan; Vijay Khanderao Mahadik (Asian Journal of Medical Sciences, 2022)
Background: It was hypothesized that electrical vestibular nerve stimulation (VeNs) was an effective therapy in the management of obesity. Aims and Objectives: The present pilot study was undertaken to observe the efficacy of 12-week electrical VeNs in the management of obesity. Materials and Methods: As this is a pilot study, a total of ten obese male and female participants were recruited after obtaining written, informed consent. After recording the baseline values, electrical VeNs was administered as an intervention for 12 weeks. The post-interventional assessment was done after 12 weeks. Results: There was a significant decrease in the serum cholesterol, VLDL, and HbA1C followed by the vestibular stimulation for 12 weeks. Although the body weight was decreased, it was not statistically significant. Conclusion: The present pilot study results support the positive impact of electrical VeNs in the management of obesity. Further, detailed studies with higher sample size were recommended to provide adequate scientific evidence to adopt electrical VeNs as an alternative therapy for the management of obesity.